Grid Impedance Measurement, Addressing Uncertainty - Fang, Jiayu; Yang, Shuying (2023 IEEE PELS Students and Young Professionals Symposium (SYPS), 2023)
Small signal stability judgement and improvement of the grid-tied inverters are important, while the knowledge of the grid impedance over wide frequency range is necessary in such process. The measurement of impedance, i.e., the small signal characteristic, is mainly based on signal injection method and subject to the following problems. Firstly, the harmonics from the grid and the inverter threat the measurement accuracy. Second, the limited DSP memory space restricts the frequency resolution of the discrete Fourier transform (DFT) making the impedance of some frequency range hard to calculate. Thirdly, uncertainty of the grid, i.e., the equivalent time constant, makes the injection and the data collection difficult. These problems have not been well resolved, according to the limited knowledge of the authors. Hence, this paper discusses these problems theoretically and proposes a method to overcome them.